Validation of the ICD/AIS MAP for pediatric use. Issue 2 (1st June 2001) - Durbin, D R; Localio, A R; MacKenzie, E J
Abstract : Objective —To determine the performance of the ICD/AIS MAP (© E J MacKenzie et al ) as a method of classifying injury severity for children. Methods —Data on all children less than 16 years of age admitted to all designated trauma centers in Pennsylvania from January 1994 through October 1996 were obtained from the state trauma registry. The ICD/AIS MAP was used to convert all injury related ICD-9-CM diagnosis codes into abbreviated injury scale (AIS) score and injury severity score (ISS). Agreement between trauma registry AIS and ISS scores and MAP generated scores was assessed using the weighted κ (κw ) coefficient for ordered data and the intraclass correlation coefficient for continuous data. Results —Agreement in ISS scores was excellent, both overall (intraclass correlation coefficient = 0.86, 95% confidence interval (CI) 0.84 to 0.89)), and when grouped into three levels of severity (κw = 0.86, 95% CI 0.85 to 0.87). Agreement in AIS scores across all body regions and ages was also excellent, (κw = 0.86 (95% CI 0.83 to 0.87). Agreement increased with age (κw = 0.78 for children <2 years; κw = 0.86 for older children) and varied by body region, though was excellent across all regions. Conclusions —The performance of the ICD/AIS MAP in assessing severity of pediatric injuries was equal to or better than previous assessments of its performance on primarily adult patients. Its performance was excellent across the pediatric age range and across nearly all body regions of injury.